The implications of electronic cigarette use on oral health: Literature review (Research, Society and Development, 2024)
Electronic Cigarettes (EC) are devices that use e-liquids to produce an aerosol that, when vaporized and subjected to high temperatures, decomposes into ketene gas, a toxic component. Studies have shown that these devices can predispose to the development of oral diseases, such as periodontitis and cavities. This work aimed to review the literature regarding the implications of electronic cigarette use on oral health. An integrative review of the literature was carried out using the Scielo, Google Scholar and PubMed/NCBI databases, including articles published in the last 10 years and resolutions made by government bodies, in Portuguese and English. It was observed that ECs directly affect the oral health of individuals, through changes caused both by irritating chemical substances and changes in temperature and pH, contributing to periodontal diseases, dental cavities, opportunistic diseases and those related to smoking and even even the development of neoplasms, as they cause genetic mutations and persistent inflammation.